Enduring enmity: explaining the absence of reconciliation between Iran and the United States - Dzulhisham, Huzeir Ezekiel (Nanyang Technological University, 2023)
Since the establishment of the Islamic Republic in 1979, the bilateral relationship between the Islamic Republic of Iran and the United States of America has been unreconciled for 44 years. During this period both states possessed no formal diplomatic relations, even worse the bilateral relationship has been plagued by mutual hostility and marred by conflict. Yet this relationship has critical international implications, as the Middle East is centrally situated on major trade routes and represents the nexus of the world’s energy supplies. Existing scholarship has attributed this phenomenon either to traumatic history, incompatible ideologies or the competition for hegemony. Despite the contributions of these explanations, they remain fundamentally incomplete due to myopic focus and neglect recognition of other salient sources of conflict. This forms the basis of this dissertation’s enquiry: why is there an absence of reconciliation between Iran and the United States? This dissertation argues that unreconciled relations and persistent hostility and conflict between Iran and the US can be explained by neoclassical realism and is the product of three variables: exogenous political influences, threat perceptions, and the domestic mobilisation of history. Collectively, these variables influence the regime behaviours of both Iran and the US by creating constraints on reconciliation, as well as providing incentives for aggressive regime behaviour and conflict. Therefore this dissertation provides a multifaceted, structure and agent-based approach to explain persistent unreconciled Iran-US relations, and also reveals underlying sources of conflict that apply to other longstanding conflicts in the international system.